The Influence of Fear of Missing Out (FoMO) and Impulsive Buying on Financial Management Behavior among University Students - Nurul Adha Azzahri; Oknaryana Oknaryana (Universitas Negeri Padang, 2026)
Financial management behavior has become a crucial issue among college students, particularly in the digital era where social media can influence consumption decisions. This study examines the relationship between Fear of Missing Out (FoMO), impulsive buying, and financial management behavior among students of the Faculty of Economics and Business, Padang State University. A quantitative approach was adopted using purposive sampling. This study used a quantitative approach with a population of 3,163 active students at the Faculty of Economics and Business, Padang State University, involving 97 respondents. Data were analyzed through path analysis with IBM SPSS Statistics. The results showed that FoMO and impulsive buying did not significantly influence financial management behavior. Instead, FoMO was found to significantly increase impulsive buying, while the indirect effect of FoMO on financial management behavior through impulsive buying was not supported. The proposed model explained 35.2% of the variance in impulsive buying and 3.8% of the variance in financial management behavior. These findings suggest that FoMO primarily influences consumption-related behavior rather than financial management behavior. Therefore, strengthening financial literacy should be complemented by educational initiatives that increase students' awareness of the psychological factors that influence consumption decisions.